Correlating the skewness and kurtosis of baryon number distributions - Fu, Wei-jie; Pawlowski, Jan M. (Physical review, 2016)
The skewness and the kurtosis of the baryon number distributions are computed within QCD-improved low energy effective models including quantum thermal and density fluctuations. The results are compared with the Beam Energy Scan experiment at RHIC. The theoretical results agree with the experimental measurements up to errors, for the collision energy √s≥19.6 GeV. For smaller collision energies a discrepancy between theoretical and experimental results develops. This discrepancy partially relates to the lack of precision of the current setup for small collision energies. It is outlined how this deficiency can be overcome.